(untitled) (Palimpsesto, 2020)
In this text we deal with an essay-novel by the Puerto Rican writer, Eduardo Lalo, entitled The Invisible Countries. In order to read the plurality of meanings of this work, we have resorted to a metaphorical use of the archive concept. In order to reach that metaphorical level it has been necessary to take a tour of other ways of conceiving the archive and the various functions that have had in different spaces. We deal with a set consisting of seeing, knowing and power that affects the culture of eccentric countries. Visibility or invisibility is not a simple physical issue that gets intensely involved with the indicated triad. Lalo tries to oppose the increasing invisibility of the "minor" countries a vanishing point that makes geographical eccentricity an advantage by configuring a new place of writing, that is, the interstitium that the West leaves as a result of its blindness for everything that is not canonically his own.